A Comparative Map of the Zebrafish Genome - Woods, Ian G.; Kelly, Peter D.; Chu, Felicia; Ngo-Hazelett, Phuong; Yan, Yi-Lin; Huang, Hui; Postlethwait, John H.; Talbot, William S.

(untitled) (Genome Research, 2000)
Zebrafish mutations define the functions of hundreds of essential genes in the vertebrate genome. To accelerate the molecular analysis of zebrafish mutations and to facilitate comparisons among the genomes of zebrafish and other vertebrates, we used a homozygous diploid meiotic mapping panel to localize polymorphisms in 691 previously unmapped genes and expressed sequence tags (ESTs). Together with earlier efforts, this work raises the total number of markers scored in the mapping panel to 2119, including 1503 genes and ESTs and 616 previously characterized simple-sequence length polymorphisms. Sequence analysis of zebrafish genes mapped in this study and in prior work identified putative human orthologs for 804 zebrafish genes and ESTs. Map comparisons revealed 139 new conserved syntenies, in which two or more genes are on the same chromosome in zebrafish and human. Although some conserved syntenies are quite large, there were changes in gene order within conserved groups, apparently reflecting the relatively frequent occurrence of inversions and other intrachromosomal rearrangements since the divergence of teleost and tetrapod ancestors. Comparative mapping also shows that there is not a one-to-one correspondence between zebrafish and human chromosomes. Mapping of duplicate gene pairs identified segments of 20 linkage groups that may have arisen during a genome duplication that occurred early in the evolution of teleosts after the divergence of teleost and mammalian ancestors. This comparative map will accelerate the molecular analysis of zebrafish mutations and enhance the understanding of the evolution of the vertebrate genome.